Molecular Genetic Analysis of Steroid Resistant Nephrotic Syndrome, Detection of a Novel Mutation (Iranian Journal of Kidney Diseases, 2019)
Introduction. Nephrotic syndrome is a heterogeneous disease in children, with nearly 10% categorized as steroid-resistant. In this study we evaluated disease related mutations within NPHS1, NPHS2 and new potential variants in other genes. Methods. In the first phase of study, 25 patients with SRNS were analyzed by Sanger sequencing for NPHS1 (exon 2, 26) and all exons of NPHS2 genes. In the next step, whole exome sequencing was performed on 10 patients with no mutation in NPHS1 and NPHS2. Results. WES analysis revealed a novel mutation in FAT1 (c.10570C > A; Q3524K). We identified 4 pathogenic mutations, located in exon 4 and 5 of NPHS2 gene in 20% of patients (V180M, P118L, R168C and Leu156Phe). Also our study has contributed to the description of previously known pathogenic mutations across WT1 (R205C) and SMARCAL1 (R764Q) and a novel polymorphism in CRB2. Conclusion. It seems that NPHS2, especially exons 4 and 5, should be considered as the first step in genetic evaluation of Iranian patients. We suggest conducting WES after NPHS2 screening to identify the potential genes associated with SRNS, Further studies are required to examine more common genes in the first step and then designing native laboratory panels.